K.H. HASYIM ASY'ARI AND INDONESIAN FIQH: SOCIO-COMMUNITY ANALYSIS IN BOOK ARBA'IN HADITHAN IN RESPONSE TO CONTEMPORARY ISSUES - Imani, Fachri Rizki; Muhammad Fikri Adrian; Dzulkifli Hadi Imawan (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - This study aims to analyze the societal principles of K.H. Hasyim Asy'ari (1871-1947 CE) in his monumental work, Arba'in Hadithan Tata'allaq bi Mabadi Nahdlat al-Ulama. The main focus of this study is how the traditions collected in the book represent social principles and their relevance in contemporary Islamic law and fiqh of the archipelago. The study also explores the tradition of writing forty hadith in Islamic history and the contribution of K.H. Hasyim Asy'ari in enriching the intellectual treasures of Islam in Indonesia. Methods - This research uses the content analysis method with a qualitative approach. The data were analyzed systematically to identify the social principles summarized in the Book of Arba'in Hadithan. This research also pays attention to the historical aspects of hadith codification and the development of Islamic thought in the archipelago. Findings - The study results showed that the tradition of writing forty traditions has been going on since the beginning of the codification of hadith until the time of K.H. Hasyim Asy'ari. The Book of Arba'in Hadithan contains societal principles that emphasize the values of togetherness, justice, and welfare. The hadiths discussed in this book are relevant to contemporary Islamic law and Indonesian fiqh. Contribution/Limitation - This research contributes to understanding the relevance of K.H. Hasyim Asy'ari's thoughts to contemporary Islamic law, especially in Nusantara fiqh. However, this research is still limited to analyzing the Arba'in Hadithan book and has not examined comparisons with other books. Originality/Value - This research enriches the insight into the writing tradition of Nusantara scholars and their contributions to Islamic law. The findings can be a reference for academics and practitioners studying Indonesian fiqh.